RWP Pelatihan Produksi Konten Pada Media Instagram Sebagai Penyampaian Informasi Di SMK Letris Indonesia Tangerang Selatan - Jeanie Annissa; Ricky Widyananda Putra (CV. Multi Kreasi Media, 2022)
Today, technology is growing rapidly in its use to help human life. The result of technological developments that we often encounter and even we ourselves may each have is a mobile phone or cellphone. This object is always in our hands at all times. In a day, we almost never miss the features that make it easy to communicate. Moreover, mobile phones now with advanced technology and interesting applications. For example, the use of social media that is widely used by young people today, Facebook, Twitter and Instagram. One of the social media that is often used by millennials today is Instagram, through this media we can convey information and will also be closer to things that interest us, by following an account. Everything feels so easy and practical with technology and the internet. Based on the above and in order to increase the ability (skills) of students at SMK Letris Indonesia, Jl. Kalimantan 1 Villa Bintaro Indah Jombang – Ciputat, South Tangerang, where the school wants to hold a training aimed at using Digital Media as a medium for delivering information to the wider community. This is one of the skills that students want to improve so that they are able to create creative content, especially using Instagram media. So that later they can maximize the delivery of a flow of information to the public.